What makes good science? Information literacy seminars as a means to stimulate reflection among PhD students - Andreassen, Helene N.; Østvand, Lene (2016)
Conference: Creating Knowledge VIII Organizers: NordINFOLIT Reykjavík, 2.-3. June 2016 In addition to the demanding task of writing a thesis, PhD students face the challenge of balancing the roles as “good scientists” and “good academics”, which in some cases might conflict (Carter, 2015). They are expected to carry out a laborious research project where they are responsible for keeping in line with the norms and values of research ethics, all while building the foundation for their research career, where a “publish or perish” culture is currently ruling. Information literacy teaching has experienced a shift in focus in latter years. If libraries traditionally have devoted their time to teaching undergraduate students the hows of using sources, they now spend more time on the whys and the importance of being information literate for the acquisition of knowledge. At our university, this shift has further led to reflection upon how the information literacy needs persist, but gradually change, from undergraduate to PhD level. In 2015, to meet the needs of the latter, we launched the cross-disciplinary seminar series Take control of your PhD journey (cf. https://uit.no/ub/laringsstotte#linje2). Presently, researchers are highly encouraged to publish text and research data open access, thereby contributing to the integrity and transparency of science. In this presentation, on the basis of open-ended questionnaire data collected during Spring-2016, we aim to assess to which degree our PhD students reflect and act upon academic integrity and open access, and their possible conflict with assumed career-building measures. In light of these findings, we discuss whether or not PhD students are sufficiently aware of this challenge, and further, which actions should be taken by university libraries to help them meet the expectations of present-day academia.